Habituation of Family Assistance on Early Reading Ability of Grade VI Students at State Elementary School Cijoro Lebak - Maslihah Zahroh Agustina; Dase Erwin Juansah; Ikman Nur Rahman (MASI Mandiri Edukasi, 2026)
This study investigates the role of family-based habituation in developing early reading skills among Grade VI students at SDN 1 Cijoro Lebak, focusing on how parental involvement contributes to students’ reading courage, self-confidence, reading initiative, and reading fluency. A qualitative case study design was employed, with data collected through interviews, observations, and documentation, and analyzed using NVivo 12 through coding and visualization techniques such as word cloud, project map, matrix coding, and tree map analysis. The findings show that family habituation is implemented through structured study schedules, parental supervision, motivational support, rewards, and restrictions on mobile phone use, which together create a consistent home literacy environment that encourages repeated reading practice. The results indicate significant improvements in students’ early reading skills, particularly in confidence, independence, and fluency, as students gradually shift from dependent readers to more autonomous learners. The study concludes that family involvement plays a crucial role in shaping early literacy development, as supported by Bronfenbrenner’s Ecological Systems Theory, Family Literacy Theory, and Bourdieu’s Theory of Habitus, all of which emphasize that reading development is strongly influenced by continuous interaction within the family environment.